Diseño y construcción de un mecanismo pendular de accionamiento manual para un sistema de bombeo de 20 l/h de agua y elevación de un metro (2020)
In the following document, a problem that arises in the Colombian territory is raised, such as the lack of devices or systems for supplying drinking water that are easily accessible to families with very low economic resources. build a device that is capable of supplying drinking water and that is also very easy to access. An analysis is carried out with some proposed alternatives for the design and selection of the mechanism to be developed. The document supports the construction phase that was developed throughout the project, in which design calculations, material selection and the process of construction of the mechanism, in addition a test phase that was developed to evaluate the performance of the mechanism is attached.